Clinical Pharmacogenetics Implementation Consortium (CPIC) Guideline for CYP2D6 and CYP2C19 Genotypes and Dosing of Selective Serotonin Reuptake Inhibitors. Issue 2 (29th June 2015) - Hicks, JK; Bishop, JR; Sangkuhl, K; Müller, DJ; Ji, Y; Leckband, SG; Leeder, JS; Graham, RL; Chiulli, DL; LLerena, A; Skaar, TC; Scott, SA; et al.
<x xml:space="preserve">Abstract</x> Selective serotonin reuptake inhibitors (SSRIs) are primary treatment options for major depressive and anxiety disorders. CYP2D6 and CYP2C19 polymorphisms can influence the metabolism of SSRIs, thereby affecting drug efficacy and safety. We summarize evidence from the published literature supporting these associations and provide dosing recommendations for fluvoxamine, paroxetine, citalopram, escitalopram, and sertraline based on CYP2D6 and/or CYP2C19 genotype (updates at www.pharmgkb.org).